2008
DOI: 10.1086/587492
|View full text |Cite
|
Sign up to set email alerts
|

HIV‐1 Tropism and Survival in Vertically Infected Ugandan Infants

Abstract: Complex patterns of HIV tropism were found in HIV-infected newborn infants. Subtype D infection was associated with X4 virus and with high-level replication in CCR5-bearing cells. High-level replication of R5 virus was associated with decreased infant survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
23
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 34 publications
7
23
0
Order By: Relevance
“…These studies demonstrate that early virus isolates from plasma samples within the first 4 months of life in P and SP infants have marked differences in viral RC. We show that SP infants typically have virus with a low RC, which is consistent with an important influence of viral attenuation on pediatric HIV progression and is consistent with recently published data in D clade infected infants showing an association between viral infectivity and survival during infancy (7). Although in general there was a concordance between measurements of the RC and infectivity determined by replication kinetics and single-cycle infectivity, in some instances this was not the case.…”
Section: Discussionsupporting
confidence: 91%
“…These studies demonstrate that early virus isolates from plasma samples within the first 4 months of life in P and SP infants have marked differences in viral RC. We show that SP infants typically have virus with a low RC, which is consistent with an important influence of viral attenuation on pediatric HIV progression and is consistent with recently published data in D clade infected infants showing an association between viral infectivity and survival during infancy (7). Although in general there was a concordance between measurements of the RC and infectivity determined by replication kinetics and single-cycle infectivity, in some instances this was not the case.…”
Section: Discussionsupporting
confidence: 91%
“…Unfortunately, no follow-up information was available for the other five subjects in this study. Based on observations in sexual transmission reported here and vertical transmission reported elsewhere, 30 we speculate that in addition to evolution from R5-tropic viruses, the emergence of CXCR4-using viruses during later stages of HIV-1 infection could, in some cases, result from the outgrowth of transmitted CXCR4-using variants.…”
Section: Huang Et Alsupporting
confidence: 68%
“…25 An 8% frequency of X4 variants among infants in our study is quite comparable to the 9% observed in a Ugandan study with subtypes A and D-infected infants. Similarly, survival of the infants with the R5 variant was not significantly different from survival of the infants with X4 variants as also observed by Church et al 26 Generally studies have shown that children can progress to AIDS without evidence of X4 virus, and some with X4 variants can remain asymptomatic for more than 1 year. 27 Of the three more recently infected mothers with acute HIV-1 infection, one had R5 genotypes as expected since the X4 genotype is normally associated with advanced disease or is more common in patients receiving antiretroviral therapy.…”
Section: Discussionsupporting
confidence: 72%